AIPLE-IS: An Approach to Develop Product Lines for Information Systems Using Aspects - Braga, Rosana T. Vaccare; Germano, Fernão S. Rodrigues; Pacios, Stanley F.; Masiero, Paulo C. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2007: Anais do I Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2007)
Product lines for information systems present variabilities both in non-functional and functional features. Aspects are being used successfully in the implementation of non-functional features, as they provide intuitive units for isolating the requirements associated to this type of features. However, aspects could also be used to implement some product line features that refer to functional requirements. Using that approach, the instantiation of specific products could be done by combining the desired aspects into the final product. In this paper, we propose an approach, named AIPLE-IS, to incrementally build a product line for information systems using aspects. The product line core is developed first, followed by the addition of optional features through aspects. A case study for a product line in the domain of information systems for psychology clinics is presented to illustrate the approach.